2014
DOI: 10.1002/cncr.29089
|View full text |Cite
|
Sign up to set email alerts
|

Clinical next‐generation sequencing in patients with non–small cell lung cancer

Abstract: BACKGROUND: A clinical assay was implemented to perform next-generation sequencing (NGS) of genes commonly mutated in multiple cancer types. This report describes the feasibility and diagnostic yield of this assay in 381 consecutive patients with non-small cell lung cancer (NSCLC). METHODS: Clinical targeted sequencing of 23 genes was performed with DNA from formalin-fixed, paraffin-embedded (FFPE) tumor tissue. The assay used Agilent SureSelect hybrid capture followed by Illumina HiSeq 2000, MiSeq, or HiSeq 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(174 citation statements)
references
References 24 publications
(45 reference statements)
9
161
0
Order By: Relevance
“…Novel research techniques, such as next generation sequencing, have been developed (1,2) and the usage of DNA from stored formalin-fixed and paraffin-embedded (FFPE) tissues libraries has increased. For example, comprehensive analysis of DNA alteration with next generation sequencing enables us to identify the novel genomic alterations in patients with cancer recurrence, which may provide more therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Novel research techniques, such as next generation sequencing, have been developed (1,2) and the usage of DNA from stored formalin-fixed and paraffin-embedded (FFPE) tissues libraries has increased. For example, comprehensive analysis of DNA alteration with next generation sequencing enables us to identify the novel genomic alterations in patients with cancer recurrence, which may provide more therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Yet studies have also demonstrated the risk of artifacts which can cause false-positive results from challenging cancer biopsies such as FFPE specimens [2][3][4][5]12,14 . Additionally, recent publications have highlighted high failure rates for NGS using oncology specimens 16 and false-positive calls with commercial targeted NGS panels that are aggravated by the use of low-input DNA 12 . As a result, some laboratories have either modified or added additional checks and balances to commercially available targeted NGS technologies to improve performance, often to ensure accuracy or confirm the findings from the bioinformatic analyses 5,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the expansion of numbers of these gene alterations seems to pose some problems. One of these problems that need to be surmounted is the necessarily longer time required to interpret data on whole gene sequences [144]. Another problem pertains to generating a readable report of the alterations that are identified For tissue biopsies and cell blocks, serial sections should be cut, and HE-stained sections need to be analyzed by experienced pathologists to formulate definitive histologic diagnoses and evaluate the tumor cellularity.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%